2014
DOI: 10.1007/s00414-014-1112-z
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation in children and young adolescents for forensic purposes using fourth cervical vertebra (C4)

Abstract: The aim of this study was to evaluate the applicability of using the growth of the body of C4 vertebra for the estimation of age in children and young adolescents. We used the fact that the proportions between the radiologic projections of the posterior and anterior sides of the C4 vertebral body, which forms a trapezoidal shape, differ with age: in younger individuals, the posterior side is higher, whereas in older individuals, the projections of the sides of the vertebral body form a rectangular shape with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 49 publications
0
24
0
7
Order By: Relevance
“…Their studies demonstrated that the assessment of medial clavicle ossification by CT must be realized on thin-slice CT examinations, with an experienced observer [5,[7][8][9]. Other bone structures were also tested in age estimation, like radiographic study on cervical spine [10]. MR studies tend to increase in frequency, according to cross-sectional imaging increasing performances.…”
Section: Introductionmentioning
confidence: 99%
“…Their studies demonstrated that the assessment of medial clavicle ossification by CT must be realized on thin-slice CT examinations, with an experienced observer [5,[7][8][9]. Other bone structures were also tested in age estimation, like radiographic study on cervical spine [10]. MR studies tend to increase in frequency, according to cross-sectional imaging increasing performances.…”
Section: Introductionmentioning
confidence: 99%
“…Mais recentemente, a união do anel vertebral cervical demonstrou correlação moderada com a conhecida idade da morte. Essa união ocorre mais precocemente nas mulheres e pode ajudar a estimar a idade juntamente com outros indicadores presentes nos remanescentes ósseos 49 .…”
Section: Ossos Do Pescoçounclassified
“…[12][13][14] Others have studied the geometry of stages of the cervical vertebrae -that is, the relationship between the growth of the vertebrae and the age of children and young adolescents -for forensic purposes. [15][16][17] The growth of the cervical vertebrae follows a somatic pattern and they reach their final maturation at approximately 15-16 years, with the maximum cervical vertebral growth rate at between 10 and 12 years. 18 To the best of our knowledge, there is no evidence in the scientific literature regarding the use of CVM stages to predict the attainment of legal age thresholds.…”
Section: Introductionmentioning
confidence: 99%